Get Ahead with Quizizz: Advancing Junior High School Students' Vocabulary Mastery in Online Learning. - Maming, Khadijah; Sani, Ahliana Afifati; Putra, Dany Prima; Radiana, Sonia Permata (Elsya : Journal of English Language Studies, 2023)
This experimental study examines the effectiveness of Quizizz application in enhancing Junior High School students' vocabulary mastery. The study aims to address the problem of low scores in English vocabulary among Junior High School students, and investigates whether the use of Quizizz as an interesting and interactive media can improve their vocabulary mastery. The study employed a pre-test and post-test control group design, with 22 students in the experimental group and 23 students in the control group selected using random sampling. The experimental group received were taught using Quizizz, while the control group used other similar web-apps. Both groups received instruction in vocabulary. The study found that the use of Quizizz significantly improved students' vocabulary mastery, as evidenced by the higher mean score of the experimental group (81.68) compared to the control group (77.21). However, the study's findings are limited to Junior High School students and may not generalize to other age groups or contexts. The findings suggest that incorporating interactive and engaging online learning tools such as Quizizz can be a promising approach to addressing the problem of low scores in English vocabulary among Junior High School students. However, further research is needed to determine the generalizability of these findings to other age groups and contexts.